Identification of species, intensity, and prevalence of Vannamei shrimp (Litopenaeus vannamei) ectoparasites in traditional ponds North Gorontalo - Juliana Juliana; Yuniarti Koniyo; Ike Nursyafitri Dangkua; Indika Abd. Rahman (Depik, 2023)
Vannamei shrimp (Litopenaeus vannamei) production continues to decline due to parasitic attacks on ponds in North Gorontalo Regency. Ectoparasites are one of the factors that can cause failure in the cultivation of vannamei shrimp. This study aims to determine the type of ectoparasites, intensity, and prevalence of vannamei shrimp cultured in traditional ponds in the North Gorontalo Regency. The sampling of the research was carried out at five research stations. The sampling of this research was taken at random in 5 plots of ponds and the total number of shrimps as many as 150 tails. At each station, samples were taken of 30 vannamei shrimp. Sampling using fishing gear in the form of nets. The observed samples were 8-10 cm in size alive. Observations of ectoparasites were carried out microscopically using a Zeis Binocular microscope with 10x magnification. Data analysis used descriptive analysis of the types of ectoparasites, intensity, and, the prevalence of ectoparasites found. The results of the study found four types of ectoparasites found in vannamei shrimp, namely Zoothanium sp., Epistylis sp., Carchesium sp., and Vorticella sp. The intensity of ectoparasite attack on shrimp was categorized as low to moderate infection, namely 4-7 individuals/shrimp. The prevalence rate is 80-100% with the category of moderate to very severe infection.Keywords:EctoparasitesPrevalenceIntensityVannamei shrimp